Analisis Perbandingan Kinerja Keuangan PT Bank Rakyat Indonesia Tbk Dan Keuangan PT Bank Central Asia Tbk Pada Tahun 2021-2024 - Ariya Putra Utama; Sari Octavera (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study examines the comparison of the financial performance of PT BRI Tbk with PT BCA Tbk in 2021-2024. The study was conducted using the RGEC method. The method used in this study is a comparative qualitative approach. The data source used by the researcher is a secondary data source using the BEI data collection technique. Hypothesis testing used in this study is the Mann Witney-U analysis of IBM SPSS 23 Statistics. The results of the tests that have been carried out indicate that (1) Risk Profile (NPL) Components. Both BRI and BCA have Non-Performing Loan (NPL) ratios that fall into the healthy to very healthy category. However, BCA consistently shows a lower NPL ratio than BRI during the 2021-2024 period, which indicates that BCA's credit risk management is more effective in maintaining the quality of productive assets. (2) Good Corporate Governance (GCG) Components. BRI excels in GCG implementation because it actively participates in external assessments from independent institutions such as CGPI by IICG and SWA Magazine, and obtained a high score (95.31) and the award of “The Most Trusted Company” in 2024. Meanwhile, BCA only conducts self-assessment without actively participating in external evaluations, even though its GCG reporting is carried out routinely and systematically. (3) Earnings Component (ROA). The profitability performance of both banks is classified as very healthy, with BCA's ROA consistently higher than BRI's. This indicates that BCA is more efficient in managing its assets to generate profits, reflecting optimal operational and digitalization strategies. (4) Capital Component (CAR). Both banks demonstrate a very strong level of capitalization with a CAR ratio above 24%. BRI has a slightly higher CAR ratio than BCA, indicating that BRI has a larger capital buffer to cover potential risks, although the trend is slightly decreasing from year to year.